Cardiac specific PRMT1 ablation causes heart failure through CaMKII dysregulation - Jung-Hoon Pyun (Nature Portfolio, 2018)
The mechanisms that regulate the activity of Ca2 +/calmodulin-dependent protein kinase II (CaMKII) in the context of heart failure are incompletely understood. Here the authors show that protein arginine methyltransferase 1 (PRMT1) prevents cardiac hyperactivation of CaMKII and heart failure development by methylating CaMKII at arginine residues 9 and 275.